PENGARUH RASIO KEUANGAN DALAM MEMPREDIKSI POTENSI KEBANGKRUTAN PADA PERUSAHAAN CUSTOMER GOODS YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sagala, Lamria (UNIKA Santo Thomas, 2015)
This study aims to identify and analyze the influence of Current Ratio, Debt To Assets Ratio, Return on Assets, and Earning Per Share partially or simultaneously to the prediction of financial distress on customer goods companies listed in Indonesia Stock Exchange.The population in this study is a company customer goods listed in Indonesia Stock Exchange in 2010-2012. Of the 36 listed companies, 32 companies selected samples using purposive sampling method. The data used in this research is secondary data, to gather the information needed from www.idx.co.id and Indonesian Capital Market Directory (ICMD). This study analyzed using logistic regression analysis. The conclusion that can be drawn from this study is that the Current Ratio, Debt To Assets Ratio, Return on Assets, and earning per share has an influence on the prediction of financial distress. While only partially Debt To Assets Ratio which has a significant influence on the prediction of financial distress while the three other independentvariables have no effect on financial distress prediction.